Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I've recently come across the following equality in a paper: suppose one defines an analytic function $L(n,x)$ which is equal to the $n$th Laguerre polynomial for $n\in\{0,1,\ldots\}$, and let* $L^{(1,0)}(n,x) = \frac{\partial}{\partial n}L(n,x)$. Then apparently

$$L^{(1,0)}(-1,-x) = -[\gamma_E + \Gamma(0,-x) + \log(-x)]e^{-x}$$

where $\gamma_E$ is the Euler-Mascheroni constant and $\Gamma$ is the incomplete gamma function.

Numerically, this checks out, but I would be interested in a symbolic proof that the equality holds. I've been playing around with the generating function for the Laguerre polynomials (and some other representations), but I haven't figured out a way to make the connection. Can anyone help me out?

*$L^{(1,0)}$ is called the "multivariate Laguerre polynomial" in the paper; I couldn't find a source to tell me whether this is a widely recognized function or not.

share|cite|improve this question
$\gamma_E$ is Euler-Mascheroni, I take it. – J. M. Aug 7 '12 at 4:30
In any event, this seems to be the applicable formula. You have $$\lim_{\nu\to-1}(\pi\cot(\nu\pi)+\psi(1+\nu))=\lim_{\nu\to-1}\psi(-\nu)=-\gamma‌​$$ and the series will then evaluate in terms of the incomplete gamma function (or exponential integral, whichever you prefer). – J. M. Aug 7 '12 at 4:36
@J.M. true, I forgot to specify that. Thanks for the tip. – David Z Aug 7 '12 at 5:25
up vote 2 down vote accepted

Laguerre function is defined in terms of the hypergeometric ${}_1F_1$ as follows: $$L_\nu(x) = {}_1F_1\left(-\nu; 1; x\right)$$ Thus: $$ \left.\frac{\partial}{\partial \nu} L_\nu(z)\right|_{\nu = -1} = \sum_{n=0}^\infty \frac{(1)_n}{n!} \frac{z^n}{n!} \left( \psi(n+1) - \psi(1) \right) = \sum_{n=1}^\infty \frac{z^n}{n!} H_n = \sum_{n=1}^\infty \frac{z^n}{n!} \sum_{m=1}^n \frac{1}{m} \\= \sum_{m=1}^\infty \frac{1}{m} \sum_{n=m}^\infty \frac{z^n}{n!} = \sum_{m=1}^\infty \frac{1}{m} \mathrm{e}^z \frac{\gamma(m,z)}{\Gamma(m)} = \mathrm{e}^z \int_0^z \sum_{m=1}^\infty \frac{t^{m-1}}{m!} \mathrm{e}^{-t} \mathrm{d} t = \mathrm{e}^z \int_0^z \frac{1- \exp(-t)}{t} \mathrm{d} t = \mathrm{e}^z \left( \gamma + \log(z) + \Gamma(0,z) \right) $$

share|cite|improve this answer
Thanks, that works! I missed the connection between $L$ and the hypergeometric function. – David Z Aug 8 '12 at 3:09

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.